(untitled) (Latakia University Journal -Basic Sciences Series, 2025)
Samples were prepared from the mixed oxide Al2O3/CdO and at a specific molar ratio (Al/Cd 1-0.25 mol) by different methods, (dry ), wet, ( ) hydrothermal, ( ) the value of the surface area of ​​the dry sample reached , for the wet sample , as for the sample prepared by the hydrothermal method at a temperature of 100oC, the value reached . The effect of the hydrothermal treatment temperature 70, 100, 130, 150 oC on the properties of the tissue structure was studied, and it was found that the surface area increases for the sample treated at 100oC , and then decreases again, it is equal to the sample treated at 150oC